The extent of multi-project management implementation in the UK construction industry - M. Abdullah, Aminatuzuhariah; G., Vickridge (2000)
In the Multi-Project (M-P) environment, the aspect of complex issues is much wider than in a single project environment. For example, complexity in the M-P environment relates to those aspects concerned with the multiple interfaces between the projects, the projects and the organisation and parties involved in the projects. One such strategy that provides an environment to alleviate these complex issues is to adopt a Multi-Project Management (MPM) approach. This approach has been well recognised in various industries, but the scarce amount of literature on MPM for the construction industry implies that this approach is not well known amongst construction practitioners, especially in the UK. To test this hypothesis, a questionnaire survey, involving 155 client and client representatives, was conducted to investigate the extent of MPM implementation in the UK construction industry and to obtain opinions on the subject. Findings presented in this paper indicate that this hypothesis is true and there is a need to establish best practice in MPM, which will provide guidelines on better management of construction M-Ps for clients and clients’ representatives in the future.